Avaliação da desfluoretação de águas com coagulante de Moringa oleifera Lam e do processo de separação por membranas - Conceição, Vinicius Masquetti da (2012)
The consumption of water with high fluoride levels may result in dental or skeletal fluorosis, and other hazards to public health. In this sense, the present study evaluated the process of reducing excess fluoride contained in fluoridated synthetic water and groundwater from the coagulation/ flocculation/sedimentation (C/F/S) with aqueous extract of Moringa oleifera Lam, and the process combined with membrane filtration. Assays C/F/S were performed in "jar test", and Moringa, used in the aqueous extract at different concentrations. Water samples were fluorinated and ground synthetic sodium fluoride (NaF) at concentrations of 3.0, 5.0, 7.5 and 10.0 mg F-/L, varying the pH between 3, 7 and 9. Tests combined with microfiltration and ultrafiltration membranes, using pressures of 1 bar and 2, consisting in subjecting samples of fluorinated synthetic water initial concentration of 5.0 mg F-/L, Moringa concentration of 5 g/L and , pH7 to process C/F/S, followed by passage through micro-ultrafiltration module. The monitoring system proposed treatment was assessed through analyzes of apparent color, turbidity, pH, conductivity and fluoride before and after the tests. The results showed good efficiency values proposed for the treatment of C/F/S, and so the initial concentration of 3.0 mg/L of fluoride all residual to both the synthetic water as the water Fluorinated underground, were below the maximum established by Ordinance nº 2.914/2011 the Ministry of Health establishing the limit of 1.5 mg F-/L. The remaining residual concentration of from 5.0: 7.5 and 10.0 mg F-/L, were slightly above the law. The final pH values were within the range of neutrality. The parameters color, turbidity and conductivity end there was a slight increase in values, and a subsequent step indicated post-treatment such as the adoption of filtration. To the combined process, good results were obtained reduction fluorine, color and turbidity of the order of 83.0%, 96.0% and 98.0% respectively for the 5 kDa membrane using pressure of 2 bar. Generally, treatment processes proposed using seed extract Moringa oleifera Lam, proved to be a good alternative to the reduction of excess of fluorine in water, with a view to the use of a coagulating agent natural, biodegradable and the generation of smaller volumes of sludge, unlike what is observed with the use of chemical coagulants.